Study of local productive arrangement competitiveness of lime companies in the Curitiba Metropolitan Region - Nascimento, Luciana Taís do; Cardoso, Patrícia Alcântara; Lima, Edson Pinheiro de (Revista Gestão da Produção Operações e Sistemas, 2010)
What defines the success or failure of an organization is the implementation of its business strategies, and a correct analysis of its competitive environment. Local Productive Arrangements - APL is a cooperation ne-twork among SME promoting several advantages, such as reduced finished product transport cost per ton; bet-ter negotiation power for raw material purchases and finished products sales. The Curitiba Metropolitan Area – RMC – Lime APL is studied to better to understand how this APL can increase competitiveness in its market and to identify its structural aspects and to analyze SME competitive factors in this cooperation network. A quantitative and qualitative approach is used in the study’s first stage, aimed at gathering and systematizing socioeconomic data. In the second stage, the collected information is essentially qualitative by nature, compri-sing descriptive issues. This study indicated that although the RMC Lime industry is recognized as an APL by government, the businessmen don’t benefit from available APL advantages, because they don’t have technical knowledge of the subject, or there is no interest in doing business through cooperation arrangements Keywords: Lime; Cluster; Competitiveness.